Pengaruh Dukungan Sosial terhadap Kepercayaan Diri bagi Peserta Didik di SMA Negeri 100 Jakarta - Rizki Adiyansah; Budiaman Budiaman; Nandi Kurniawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research have a purpose to prove the influence of social support on self confidence of students at SMAN 100 Jakarta. This research was motivated by the large number of students who feel inferior or lack self-confidence so that it can interfere with and hinder the improvement of their achievements, skills, or interests both academically and non-academically. Quantitative with a sampling technique, namely simple random sampling, is the foundation of this study. Students of SMA Negeri 100 Jakarta class 10 became the population in the study conducted. With an R Square value of 0.512, it proves that there is an influence of social support on self-confidence which is presented at 51.2%, while 48.8% is the contribution of variables other than social support such as self-concept which the researcher did not include in this study. The findings are reinforced by the t-test analysis value with an acquisition of 15.928> 1.978 which can be concluded that there is an influence of social support on the self-confidence of class X students at SMA Negeri 100 Jakarta.